MANAJEMEN ASUHAN KEBIDANAN PERIMENOPAUSE PADA NY “S” DENGAN OLIGOMENORE DI PUSKESMAS PATTALLASSANG KAB. TAKALAR - Reza Selviana Nur; Anieq Mumthi’ah Al-Kautzar; Andi Dian Diarfah (Prodi Kebidanan Universitas Islam Negeri Alauddin Makassar, 2022)
Introduction Perimenopause refers to the period during which the women’s body makes the natural transition to menopuse, marking the end of the reproductive years. Perimenopause is characterized by several symptoms including irregular menstrual cycles, hot flushes, and sleep disturbances. Moreover, during perimenopasue, women with oligomenorrhea need midwifery care in order to overcome the effects of a prolonged menstrual cycle such as the feeling of anxiety. Therefore, based on the aforementioned proble, the major purpose of this study was to investigate and conduct Perimenopausal Midwifery Care Management on Mrs “S” with the case of oligomenorrhea at Pattallassang Health Center of Takalar Regency. Method The research was conducted according to the 7-stages Varney management approach. Result The findings of this study indicated that there were no obstacles found during the care and treatment given to Mrs “S”. However, by the time the care was given, the patient occasionally complained to be feeling hot. She had also experienced sleeping troubles at night. Subsequently, after the treatment and counseling were give, the patient understood her condition and tried to recover by the assistances of the health workers. Conclusion This study concluded that in general, the condition of the patient was considered to be good. She experienced composmentis consciousness, and her vital signs were within normal limits. Moreover, the results of her physical examination showed no signs of abnormalities. Therefore, it could be suggested that there were no major problems found on the case of Mrs “S” with her oligomenorrhea. Hence, the findings of this study are in accordance with theories related to midwifery care management.